Tax Mechanism to Counteract Business Fragmentation in Agriculture - Anna V. Tikhonova; Marina V. Pyanova (Финансовый журнал)
The subject of this study is tax risks of agricultural producers associated with business fragmentation. The purpose of the study is to develop proposals for improving taxation and tax control in agriculture, contributing to the reduction of business fragmentation risks. The specific features of taxation in agriculture is conditioned by the mandatory compliance with the share of qualifying revenue from the sale of agricultural products and products of their primary and subsequent processing. This leads to the risk of business fragmentation for dishonest taxpayers. The authors analyze general approaches to identifying business fragmentation schemes and identify the criteria for artificial business fragmentation on the basis of arbitration practice materials and clarifications of the Federal Tax Service. А typical splitting scheme in agriculture is presented and disclosed. It is derived from tax incentives and preferences in agriculture, systematized in tabular form. The existing concept of risk-based approach of tax authorities does not contain special industry criteria. The study proposes a three-element mechanism for preventing splitting risks in agriculture and develops criteria for identifying illegal tax optimization schemes in the industry. The proposed mechanism includes simplification of the procedure for the application of tax incentives; establishment of indicators of “voluntary” use of benefits in agriculture; strengthening of tax control over transactions involving business splitting. The proposals contribute to a more effective implementation of the following classical and modern principles of taxation: fairness, equal competition, plurality of taxation in the sectoral context. The scientific novelty of the research lies in the comprehensive development of a new methodological approach to the formation of a mechanism for preventing the risks of business fragmentation in agriculture, taking into account the current capabilities of tax authorities and sectoral features of the economy. The practical significance of the study lies in the possibility of using the authors’ proposals by the Ministry of Agriculture and the Federal Tax Service of Russia when elaborating measures for the development of agriculture and sectoral tax control.